S2-Alar-Iliac Screw Fixation versus Iliac Screw Fixation in the Treatment of Sacral Fractures - Yangxing Luo; Yue Li; Li He; Chengla Yi (Journal of Investigative Surgery, 2022)
Purpose To compare the short-term therapeutic effects of S2-alar-iliac (S2AI) screw fixation and iliac screw fixation techniques in managing sacral fractures. Methods From September 2015 to May 2020, 42 patients with sacral fractures who underwent lumbopelvic fixation by a single surgeon were analyzed. The patients were divided into the S2AI screw group (19 patients) and the iliac screw group (23 patients). Operative data, reduction quality, postoperative complications, and functional outcomes were evaluated. Results The incidence of unplanned reoperation was significantly different between patients treated with S2AI screws than in those treated with iliac screws (0 versus 6, p = 0.02). The mean intraoperative estimated blood loss was 405.26 ± 229.67 mL in the S2AI screw group and 539.13 ± 246.32 mL in the iliac screw group (P = 0.08). No significant difference was observed in either group regarding the quality of reduction, functional outcome, or low back pain. The reduction quality based on the Matta criteria and excellent/good outcomes were 21/2 in the iliac screw group and 17/2 in the S2AI screw group. The functional outcomes based on the Majeed score and excellent/good/fair outcomes were 17/3/3 in the iliac screw group and 17/1/1 in the S2AI screw group. No complications, including implant breakage, loosening of the implant, or loss of reduction were found in either group during follow-up. Conclusion Both S2AI screws and iliac screws were effective in the treatment of sacral fractures. The use of S2AI screws, however, was independently associated with fewer unplanned reoperations for surgical site infection, wound dehiscence, and symptoms of screw protrusion than the use of iliac screws.